THE ROLE OF RESEARCH-BASED LEARNING IN HIGHER EDUCATION INSTITUTIONS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Research-based learning has become an essential approach in higher education institutions, promoting deeper understanding, critical thinking, and independent inquiry among students. By integrating research activities into the curriculum, universities encourage learners to engage actively with knowledge production rather than passively absorbing information. This method fosters analytical skills, creativity, and a sense of academic ownership, preparing students for professional and academic careers. Research-based learning also strengthens the connection between teaching and scholarly activity, enriching the overall educational experience for both students and faculty. As global demands for innovation and evidence-based decision-making grow, higher education institutions must prioritize research-led pedagogies to cultivate adaptable, skilled graduates. This article explores the significance, benefits, and challenges of implementing research-based learning and suggests strategies for effective integration into various academic programs.